Evaluation of the Capillary Blood Glucose Self-monitoring Program - Mariana Cristina Augusto; Maria José Trevizani Nitsche; Cristina Maria Garcia de Lima Parada; Maria Lúcia Zanetti; Maria Antonieta de Barros Leite Carvalhaes (Universidade de São Paulo, 2014)
OBJECTIVE: to evaluate the structure, process and results of the Capillary Blood Glucose Self-monitoring Program in a Brazilian city.METHOD: epidemiological, cross-sectional study. The methodological framework of Donabedian was used to construct indicators of structure, process and outcome. A random sample (n = 288) of users enrolled and 96 health professionals who worked in the program was studied. Two questionnaires were used that were constructed for this study, one for professionals and one for users, both containing data for the evaluation of structure, process and outcome. Anthropometric measures and laboratory results were collected by consulting the patients' health records. The analysis involved descriptive statistics.RESULTS: most of the professionals were not qualified to work in the program and were not knowledgeable about the set of criteria for patient registration. None of the patients received complete and correct orientations about the program and the percentage with skills to perform conducts autonomously was 10%. As regards the result indicators, 86.4% of the patients and 81.3% of the professionals evaluated the program positively.CONCLUSION: the evaluation indicators designed revealed that one of the main objectives of the program, self-care skills, has not been achieved.